The Role of Aqidah and Moral Teachers in Instilling Sufi Values in Students at SMA Muhammadiyah 5 Yogyakarta - Abdullah, Nasir (Universitas Muhammadiyah Yogyakarta, 2024)
This article was based on the researcher's interview regarding the decline of moral quality at a high school in Yogyakarta (SMA Muhammadiyah 5), which urges the implementation of Sufism values. The objectives of this study are to investigate (1) the learning process of aqidah and morals in SMA Muhammadiyah 5 Yogyakarta, (2) the role of Aqidah and Morals teachers in instilling the values of Tasawuf (Sufism) in students at SMA Muhammadiyah 5 Yogyakarta, and (3) the supporting and inhibiting factors for the Aqidah and Morals teachers in instilling the Tasawuf values on students at SMA Muhammadiyah 5 Yogyakarta. The study was conducted with a qualitative approach for descriptive field research. The research subjects were the school's principal, Aqidah and Morals teachers, and two students. The data collection techniques used were interviews, observations, and documentation, while the data analysis methods used were data reduction, interpretation, and conclusion drawing. The study found that (1) each teacher has different teaching methods, yet always puts good value in every process, (2) the role of the Aqidah and Morals teachers in instilling the values of Tasawuf has been carried out by guiding, facilitating, motivating, and evaluating the students, and (3) the supporting factors are schools with Muhammadiyah identity, school's vision and mission, supporting activities, role of teachers and parents as role models, positive environment, and the support from agencies, and foundations. Meanwhile, the inhibiting factors are the heterogeneous state of students, limited teacher supervision, the student community, which is far from good values, and the educators' and students' low level of human resources.